PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wisnu Wardana; Jubi Jubi; Ady Inrawan; Musa Fernando Silaen (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The results of this study can be summarized as follows, the average CTO tends to decrease, the average RTO tends to increase, the average ITO tends to decrease and the average ROA tends to decrease. The results of testing multiple linear regression are known that Cash Turnover and Inventory Turnover have a positive effect while Accounts Receivable has a negative effect on profitability in Automotive and Component Sub-Sector Companies listed on the Indonesia Stock Exchange. The correlation coefficient test results have a low relationship between Cash Turnover, Accounts Receivable Turnover and Inventory Turnover with profitability. While the coefficient of determination (R Square) states profitability is influenced by Cash Turnover, Accounts Receivable Turnover and Inventory Turnover. Cash Turnover, Receivable Turnover and Inventory Turnover have no significant effect on profitability partially. Cash Turnover, Receivable Turnover and Inventory Turnover have no significant effect on profitability simultaneously The suggestions for company in this research is that companies should optimize asset management, companies should maintain and improve cash turnover, accounts receivable turnover and inventory turnover in order to increase company profits Keywords: Cash Turnover, Receivable Turnover, Inventory Turnover and Profitability